Consensus of the Deutsche Gesellschaft der Plastischen, Rekonstruktiven und Ästhetischen Chirurgen (DGPRÄC) on Autologous Fat Grafting - Giunta, R. E.; Horch, Raymund E.; Prantl, L.; Baur, E. M.; Herold, C.; Kamolz, Lars-Peter; Lehnhardt, M.; Noah, E. M.; Rennekampff, O.; Richter, D.; Schaefer, D. J.; Ueberreiter, K. (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2016)
On occasion of the Munich Plastic Symposium in Munich the board of the Deutsche Gesellschaft der Plastischen, Rekonstruktiven und Ästhetischen Chirurgen (DGPRÄC) together with a group of experts who were also involved in the preparation of the recently published S2K guideline "Autologous Fat Grafting", prepared a consensus statement from a plastic-surgical point of view so to evaluate current spects and taking into account the current legal framework: 1. Autologous Fat Grafting is a long established treatment in plastic surgery and does not differ from other tissue grafts. 2. Mechanical processing of autologous fat does not provide any substantial change tot he tissue. 3. If other treatment methods to enrich progenitor cells of autolous fat i. e. by an enzymatic process have evidence that autologous adipose tissue or cells were substantially changed, classification as a drug could come in question under current german law (application of AMG/ATMP).
EVALuna2:32823